2011
DOI: 10.1121/1.3543943
|View full text |Cite
|
Sign up to set email alerts
|

Buckling resistance of solid shell bubbles under ultrasound

Abstract: Thin solid shell contrast agents bubbles are expected to undergo different volume oscillating behaviors when the acoustic power is increased: small oscillations when the shell remains spherical, and large oscillations when the shell buckles. Contrary to bubbles covered with thin lipidic monolayers that buckle as soon as compressed, solid shell bubbles resist compression, making the buckling transition abrupt. Numerical simulations that explicitly incorporate a shell bending modulus give the critical buckling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
76
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 31 publications
15
76
0
Order By: Relevance
“…The rupture is achieved when the shell material is elongated more than a critical elongation e max , and occurs at a pressure P buckling = 3E(d/R)e max . The experimental data were compared with the theory of Marmottant et al as shown in figure 7.4 [127]. They also stated that above a certain shell thickness/ diameter ratio, no buckling will be observed and the bubbles will only rupture while releasing their gas content, which is in perfect agreement with our observations.…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…The rupture is achieved when the shell material is elongated more than a critical elongation e max , and occurs at a pressure P buckling = 3E(d/R)e max . The experimental data were compared with the theory of Marmottant et al as shown in figure 7.4 [127]. They also stated that above a certain shell thickness/ diameter ratio, no buckling will be observed and the bubbles will only rupture while releasing their gas content, which is in perfect agreement with our observations.…”
Section: Resultssupporting
confidence: 77%
“…For the capsules with the larger shell thickness/diameter ratio this behavior was no longer observed and the capsules only responded by instant rupturing when the ultrasound pressure was above the release threshold. This behavior corresponds nicely with the recent theory of Marmottant et al [127] where they predicted the rupture and buckling threshold for varying bubble radii. When the shell thickness to bubble diameter ratio is varied, the pressure for buckling onset is predicted to vary as P buckling = E(d/R) 2 , with E the elastic Youngs modulus, d the shell thickness and R the bubble radius.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations